2015
DOI: 10.1002/cyto.a.22793
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, detection, and counting of metal nanoparticles using flow cytometry

Abstract: There is a need to accurately detect, characterize, and quantify nanoparticles in suspensions. This study helps to understand the complex interactions between similar types of nanoparticles. Before initiating a study of metal nanoparticles, five submicron PS beads with sizes between 200 nm and 1 mm were used to derive a reference scale that was useful in evaluating the flow cytometer for functionality, sensitivity, resolution, and reproducibility. Side scatter intensity (SSC) from metal nanoparticles was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…nanoscale particles). In order to relate Violet-SS to a particle size, we calibrated the flow cytometer with beads of known size (Wisgrill et al, 2016;Zucker et al, 2016). The polystyrene standard beads (200, 350, and 800 nm; qNano Calibration Particles; Izon Science, Christchurch, New Zealand, 500 and 1000 nm; Archimedes Standard polystyrene beads; Malvern Instruments, Worcestershire, UK) was suspended in ultrapure water and measured beforehand with the flow cytometer.…”
Section: Characteristic Analysis Of Nanobubblesmentioning
confidence: 99%
“…nanoscale particles). In order to relate Violet-SS to a particle size, we calibrated the flow cytometer with beads of known size (Wisgrill et al, 2016;Zucker et al, 2016). The polystyrene standard beads (200, 350, and 800 nm; qNano Calibration Particles; Izon Science, Christchurch, New Zealand, 500 and 1000 nm; Archimedes Standard polystyrene beads; Malvern Instruments, Worcestershire, UK) was suspended in ultrapure water and measured beforehand with the flow cytometer.…”
Section: Characteristic Analysis Of Nanobubblesmentioning
confidence: 99%
“…A few studies have employed flow cytometry to study nanoparticles made of polystyrene, silica, titanium dioxide, gold, or silver (1)(2)(3). A few studies have employed flow cytometry to study nanoparticles made of polystyrene, silica, titanium dioxide, gold, or silver (1)(2)(3).…”
mentioning
confidence: 99%
“…Only recently has the ability of flow cytometry been explored and exploited to also include the characterization of nanoparticles. A few studies have employed flow cytometry to study nanoparticles made of polystyrene, silica, titanium dioxide, gold, or silver (1)(2)(3). Artificial vesicles (liposomes) have also been studied (4)(5)(6)(7)(8), but the focus has largely been on assessing the enumeration, surface antigens, and size distributions of biological nano-sized vesicles known as extracellular vesicles (EVs) (8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…A previous report suggested that flow cytometry side-scatter values were suitable for observation of EVs less than 1000 nm in diameter, and in our study m/lEV size was measured by comparison with polystyrene beads [23,24]. Based on the results of NTA analysis, small materials ≤100 nm in diameter are included in fractions isolated by centrifugation.…”
Section: Discussionmentioning
confidence: 91%